2021
DOI: 10.1371/journal.pone.0247472
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plasma BMP-2, BMP-7, BMP-10, vitamin D, and TGF β1 in simple fractures among Sudanese patients

Abstract: Background Bone morphogenetic proteins (BMP) are multifunctional proteins. They work as cytokines regulating osteogenesis during fracture healing process. The objectives of this study were to assess changes in BMPs during fracture and their correlations to Fracture’s healing. Methods Case-Control hospital–based study conducted from January 2018 to January 2019. Demographic data, anthropometric measurements, and blood samples were collected from patients and controls (18–65 years old). Plasma concentrations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…In the present study, we found that the expression of BMP-7 decreased after the development of fractures, suggesting that lowly expressed BMP-7 is unable to resist injuries after fractures occur. Similarly, Ali et al[ 13 ] reported that BMP-7 was related to fractures. Furthermore, the relationship between BMP-7 and prognosis of the patient was analyzed, and the results showed that BMP-7 was correlated with the prognosis and functional recovery.…”
Section: Discussionmentioning
confidence: 98%
“…In the present study, we found that the expression of BMP-7 decreased after the development of fractures, suggesting that lowly expressed BMP-7 is unable to resist injuries after fractures occur. Similarly, Ali et al[ 13 ] reported that BMP-7 was related to fractures. Furthermore, the relationship between BMP-7 and prognosis of the patient was analyzed, and the results showed that BMP-7 was correlated with the prognosis and functional recovery.…”
Section: Discussionmentioning
confidence: 98%
“…Fracture healing is a complex biological process that involvese aspects like inflammatory response, neovascularization, and the generation of cartilage and bone tissue. Factors such as a patient’s nutritional status, circulatory status, metabolic level, and age also impact the speed and quality of fracture healing [ 18 ]. For effective healing, it’s essential to ensure the stability of the broken bone and maintenance of sufficient soft tissue coverage to provide an adequate blood supply, which helps to activate endogenous stem cells to repair damaged tissue [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 ] The concentrations of various BMPs in normal human plasma are reported to be less than 100 pg ml −1 , and it is known that the concentration of BMPs increases when fractures occur. [ 18 ] Recombinant forms of BMP, specifically BMP‐2, BMP‐4, and BMP‐7, have been shown to improve bone regeneration in animal models. [ 19 ] Of these, rhBMP‐2 and rhBMP‐7 are approved for clinical use by the Food and Drug Administration (FDA), [ 20 ] and the clinically approved doses of rhBMP‐2 and rhBMP‐7 are in the milligram range.…”
Section: Discussionmentioning
confidence: 99%